Introducing the concept of "CSF‐shift edema" in traumatic brain injury. Issue 4 (24th August 2017) - Cherian, Iype; Beltran, Margarita; Landi, Alessandro; Alafaci, Concetta; Torregrossa, Fabio; Grasso, Giovanni
Abstract: Brain edema after severe traumatic brain injury (TBI) plays an important role in the outcome and survival of injured patients. It is also one of the main targets in the therapeutic approach in the current clinical practice. To date, the pathophysiology of traumatic brain swelling is complex and, being that it is thought to be mainly cytotoxic and vasogenic in origin, not yet entirely understood. However, based on new understandings of the hydrodynamic aspects of cerebrospinal fluid (CSF), an additional mechanism of brain swelling can be considered. An increase in pressure into the subarachnoid space, secondary to traumatic subarachnoid hemorrhage, would result in a rapid shift of CSF from the cisterns, through the paravascular spaces, into the brain, resulting in an increase of brain water content. This mechanism of brain swelling would be termed as "CSF‐shift edema." This "CSF‐shift, " promoted by a pressure gradient, leads to increased pressure inside the paravascular spaces and the interstitium of the brain, disturbing the functions of the paravascular system, with implications of secondary brain injury. Cisternostomy, an emerging surgical treatment, would reverse the direction of the CSF‐shift, allowing for a decrease in brain swelling. In addition, this technique would reduce the pressure in the paravascular spaces and interstitium, leading to a recovery of the functionality of the paravascular system.